Peran Diskusi Kelompok Sebagai Ruang Komunikasi Efektif Mahasiswa KKN UNWIRA 2022 - Leuhoe, Petrus Kanisius; P. Lejap, Gracianus Edwin Tue; Bone, Matilda Pia (Universitas Gajah Putih, Indonesia, 2023)
Group discussion is a benchmark for the success of an activity that will be carried out or after the activity has been completed. The purpose of the discussion group is to encourage individual participation in the group and help the individual to investigate all opinions about the matters discussed in the activity. The service activities carried out focus on the role of discussion groups in KKN student activities. The discussions carried out resulted in various important points, including those relating to the readiness of the members, the readiness of the program and the readiness of the supporting elements of the activity. In addition, group discussions serve as a space to evaluate the progress of each activity carried out. So it can be concluded that group discussion activities are very influential on a group and efforts to achieve certain goals.